TECHNOLOGY FOR DEVELOPING VOCABULARY IN PRESCHOOL-AGE CHILDREN THROUGH PLAY ACTIVITIES - Abdiyeva Yulduz Botiraliyevna (Modern American Journals, 2025)
Speech is not only a means of communication but also a way of developing thinking and acquiring new knowledge. However, a child is not born with ready-made speech; on the contrary, speech is formed during their social life.It is no coincidence that "Mowgli" children can never achieve perfect speech. Despite the existence of sufficient literature on the formation of speech in children with various pathologies and speech disorders in general, the topic of our scientific research remains relevant.It's no coincidence that Mowglies never have perfect speech. Despite the fact that there is sufficient literature on the formation of speech in children with various pathologies and speech disorders in general, the topic of our scientific research remains relevant. The less work is done to increase the vocabulary of children with normal speech, the less work is done to increase the vocabulary of children.
Keywords: Alalia, point defect, correction, method, music therapy, articulation exercises, speech therapy game, alalia, dysarthria, exogenous, endogenous, communicative communication, emotional-volitional, pedagogical neglect.